The clinical and laboratory features of neurosyphilis in HIV-infected patients: A retrospective study in 92 patients. Issue 9 (March 2018) - Wang, Zhenyan; Liu, Li; Shen, Yin-Zhong; Zhang, Ren-Fang; Qi, Tang-Kai; Tang, Yang; Song, Wei; Chen, Jun; Lu, Hongzhou
Abstract : Abstract: Neurosyphilis (NS) is an important component of central nervous system diseases among HIV-infected patients. However, its characteristics are not very clear. A retrospective analysis of clinical and laboratory findings was performed in 92 NS patients with HIV infection from a tertiary hospital in Shanghai, China. The patients had a median age of 38 years and a median CD4 count of 198 cells/μL. In all, 44.6% (41/92) were diagnosed as asymptomatic NS (ANS), 23.9% (22/92) as syphilitic meningitis, 17.4% (16/92) as cerebrovascular NS, and 14.1% (13/92) as parenchymal syphilis. A quarter of patients (23/92) complicated with ocular syphilis (OS), 60.9% (14/23) of which were ANS. The serum tolulized red unheated serum test (TRUST) titers were ⩽1:8 in 15 patients (16.3%), 1:16–1:128 in 51 patients (55.4%), and ≥1:256 in 26 patients (28.3%). Sixty-nine patients (75.0%) had both cerebrospinal fluid (CSF) TRUST and Treponema pallidum particle assay reactive. CSF pleocytosis and protein elevation were found in 58.7% and 53.3% of patients, respectively. Syphilitic meningitis was more likely to present with CSF pleocytosis than ANS ( P  = .001), cerebrovascular NS ( P  < .001), and parenchymal NS ( P  < .001). The proportion of patients with CSF elevated protein was lower in ANS group than that in syphilitic meningitis ( P  = .003), cerebrovascular NS ( P  = .001), and parenchymal NS groups ( P  = .025), and was higher in sero-TRUST titers ⩽1:8 group than that in 1:16–1:128 ( P  = .01) and 1:256–1:1024 groups ( P  = .005). This study revealed that ANS was the most common clinical type of NS in HIV-infected patients, which should be considered in HIV and syphilis co-infection patients without neurologic symptoms, especially in those with OS. Different patterns of NS might have different CSF features which may also vary with sero-TRUST titers.